The Research Needs on Social Aspects of Biochar: A Learning from Social-Economy of Biochar Previous Study - Purnomo, Agustina Multi (Indonesian Journal of Social Research (IJSR), 2025)
Biochar has been extensively studied in terms of technical and environmental aspects. The study of social aspects of biochar was infrequent. Research on the social aspects of biochar was more often linked with technological, environmental, or economic aspects. This study utilized initial data from socioeconomic aspects because socioeconomic research was more prevalent than socio-technical or socio-environmental research. The study employed a third-step analysis analysis. First, a bibliometric analysis was conducted to examine research topics related to the social economy of biochar from published articles in Scopus and Google Scholar. Data processing was used VOSviewer and the keyword "social economy of biochar." The results were several topics studied on the social economy of biochar and the most cited articles. The second step was overlay visualization figure analysis to find trends and future research topics. The third step was comparing the keywords from the bibliometric analysis with theoretical concepts related to social aspects. The bibliometric analysis of the socioeconomic aspects of biochar revealed that research focusing on the social and economic aspects was a significant area that still needs to be completed. The majority of biochar research centers on topics related to biochar processing technology, the environment, economics, and other aspects. These findings underscore the urgent need for research on the social aspects of biochar, which remains open for social science researchers. Future research is expected to conduct a more in-depth review of published articles to address the need for studies on the social aspects of biochar.